Identification of somatostatin + inhibitory engrams for extinction in the basolateral amygdala - Xu Zhang; Zhaohui Lan; Yu Huang; Yuting Li; Zhenbo Wang; Jingyu Sun; Ying Zhou; Hechen Bao; Xuelian Fan; Jiarun Yang; Xiujuan Yang; Caiqin Li; et al. (Proceedings of the National Academy of Sciences, 2026)
The basolateral amygdala (BLA) is a key structure for processing threat and emotional information, and plays a key role in controlling the fear memory. Previous research has suggested that the extinction procedure generates a new memory that coexists with the original fear memory, and that interneurons play an important role in this process. However, the mechanisms that control the competing extinction and fear memories in BLA are not yet fully understood. To investigate these mechanisms, we developed a chemogenetic strategy that offers improved sensitivity and specificity for tagging neurons during defined behavioral epochs. This was achieved by genetically targeting GABAergic interneurons for activity-dependent manipulation, allowing us to directly probe the functional role of inhibitory ensembles recruited during fear extinction. We found that silencing extinction-tagged BLA neurons or stimulating fear acquisition-tagged BLA neurons, led to a relapse of fear memory. Additionally, we observed that silencing BLA GABAergic neurons, or more specifically, silencing the extinction-tagged BLA GABAergic neurons, restored fear expression after extinction, while inhibiting acquisition-tagged BLA GABAergic neurons did not impair fear memory retrieval. Our results indicate that specific inhibitory GABAergic BLA engrams are established during fear extinction, which interfere with existing fear memory-related neural circuits and suppress conditioned fear memory. These findings provide insights into the neural mechanisms underlying fear extinction and suggest that BLA GABAergic neurons are potential targets for therapeutic interventions in cognitive disorders such as posttraumatic stress disorder (PTSD).